Statistical Analysis of Malignant Brain Neoplasms (ICD-10: C71) in the Lower Silesia Region of Poland in the Years 2006-2012 - Robert Suslo; Piotr Nowak; Jaroslaw Drobnik (Journal of Neurological Research And Therapy, 2017)
It is crucial for the society, the government and the medical community to retrieve the full and reliable statistical information on malignant brain neoplasms (C71-C71.9 ICD-10) to adjust the medical financing, staff and equipment properly. In order to retrieve information useful for public health policies, data from the years 2006-2012 concerning relevant cases registered by the Polish public healthcare insurance provider Narodowy Fundusz Zdrowia in Lower Silesia region of Poland (NFZ) and by the Polish national neoplasms registry Krajowy Rejestr Nowotworow (KRN) were analyzed. The number of new malignant brain neoplasms cases registered by the KRN has risen slightly in the years 2006-2012. At the same time the number of cases reported by the NFZ rose dynamically, which means a significant increase in medical care intensity, and thus also workload on the medical facilities and stuff associated with the care for grossly the same amount of brain malignant neoplasms patients and, supposedly, their longer survival times. It indicates that the level of public financing of the malignant neoplasms of brain treatment shall be adjusted adequately. The study revealed growing popularity among reporting Polish physicians of the least specific malignant neoplasms of brain ICD-10 categories, despite the rapid diagnostic techniques development and availability. It is alarming since the medical statistics data quality in the field of malignant brain neoplasms is deteriorating that way and proper evaluation of treatment costs and planning future financial allocations by both the public healthcare insurance provider NFZ and the Polish government becomes difficult.
Keywords: malignant neoplasm